A DMT-Based Study on Interpreting Conceptual Metaphors from Quotations of Climate Action Discourses of Top Leaders around the UN - HOANG THI KIM, OANH (International Journal of Language and Literary Studies, 2024)
The article reports the study interpreting conceptual metaphors relating to climate crisis from the deliberate metaphors in 84 quotations of climate action discourses of top leaders around the United Nations delivered in 2023. Applying Steen’s (2008; 2023a) Deliberate Metaphor Theory and Reijnierse et al.’s (2018) Deliberate Metaphor Identification Procedure, the study interprets 19 conceptual metaphors, in which, on the schematicity levels, six conceptual metaphors are perceived on image schemata, four on domains, and nine on frames. Among those 19 conceptual metaphors (nine quotations concurrently are perceived on two levels), the five conceptual metaphors that use metaphorical expression most frequently are CLIMATE ACTION IS A JOURNEY, CLIMATE CRISIS IS DOOMSDAY, CLIMATE CRISIS IS A DESTROYER, CLIMATE CRISIS IS A WAR and CLIMATE ACTION IS CONSTRUCTION. Those 19 conceptual metaphors share the main conceptual keys stating that the climate crisis is threatening our lives to look like a war, easy to bring human being to doomsday, requiring climate action, as performing a journey, to be proceeded continuously to scramble the power of controlling the planet and convey the ideology of the UN in the movement of protecting the environment.